Decoding T cell exhaustion in the tumour microenvironment - Jin A Park; Jeyeon Im; Sung-Min Hwang (Experimental & Molecular Medicine, 2026)
Abstract T cell exhaustion arises during chronic antigen stimulation and represents a major barrier to effective anti-tumour immunity. Rather than a uniform dysfunctional state, exhaustion is increasingly understood as a structured differentiation landscape that progresses from stem-like progenitor exhausted T cells to terminally exhausted T cells. Stem-like progenitor exhausted T cells retain self-renewal capacity and partial effector function, whereas terminally exhausted T cells exhibit epigenetically fixed dysfunction and limited cytokine production. Within the tumour microenvironment, persistent antigen stimulation, together with metabolic stressors such as hypoxia and nutrient deprivation, accelerates this differentiation trajectory, thereby constraining protective immunity. In this review, we conceptualize T cell exhaustion as a dynamic continuum shaped by both differentiation states and microenvironmental niches. We outline an integrative framework to define exhaustion by combining antigen experience, cellular phenotype, functional capacity, epigenetic fixation and spatial context. Viewing immunotherapies through this multidimensional framework highlights the notion that durable therapeutic responses depend on preserving stem-like progenitor exhausted T cells within supportive niches and preventing their terminal differentiation. Understanding how these cellular states are maintained or disrupted within the tumour microenvironment will provide new opportunities for designing therapies that sustain protective T cell immunity in cancer.